Cartographic generalization and representation of objects on the map - Amangeldikyzy T Амангелдикызы Т; Zhuparkhan B Жупархан Б (Рroblems of engineering and professional education, 2023)
In the given work use ofkartographigeneralis on linearobjects is considered. Also recommendationsabout carrying out of such works and processingof results are made